ANALYSIS OF TEMPERATURE, HUMIDITY AND HOUSE ENVIRONMENTAL CONDITIONS OF LEPTOSPIROSIS PATIENTS IN WORK AREA OF BANYUANYAR COMMUNITY HEALTH CENTER SAMPANG REGENCY, EAST JAVA, INDONESIA - Sekarsari, Adinda Arum (International Journal of Psychosocial Rehabilitation, 2020)
Leptospirosis is a disease caused by Leptospira bacteria. This disease can be transmitted to humans due to contact with animals infected with Leptospira bacteria. Research Aims: This research aimed to analyze the temperature, humidity and house environmental conditions of leptospirosis patients in the work area of Banyuanyar Community Health Center Sampang Regency. Research Methods: This research was an observational research with cross sectional research design. The population in this research were leptospirosis patients in the area of Banyuanyar Community Health Center Sampang Regency. The method of taking a sample used total populated sampling that was all leptospirosis patients as many as 7 people. Temperature and humidity measurement used instruments called a Thermohygrometer and Stopwatch. Data collection was done by interviews, observations, and measurements. Data analysis used descriptive analysis The results of this research were that the total house temperature of leptospirosis patients (100%) did not qualify the requirements as well as the house humidity that did not qualify the requirements (85.7%). In the house environmental conditions of the patients, 100% of rats were found in the house of respondents affected by Leptospira. Rats in the respondents house were known based on signs of their presence such as sound, dirts, footprints, and direct appearance of the rat. Respondents affected by leptospirosis above 70% around their houses were affected by flood, conditions of overflowed sewers and the presence of puddles. This was in line with previous researchers, areas that have high flood vulnerability level will ease the Leptospira bacteria to enter the human body by swimming in flood water. The house environmental conditions of the respondents which there were floods (71.4%), puddles (85.7%), the conditions of overflowed ditch/sewer around the house (71.4%), poor dumpster conditions (57.1%). The house environmental conditions of patients had the potential to be a proliferation of Leptospira bacteria. The temperature and humidity at house of leptospirosis patients did not qualify the requirements, the houseenvironmental condition which there were presence of rats, had flood records, conditions of overflowed sewers and the presence of puddles. So that it will ease the Leptospira bacteria to enter the human body by swimming in flood water through wounds. Respondents should use dumpsters with waterproof materials and closed, routinely dispose the trash, set traps or rodenticides in places where it is potential for the rats.